Development of gelatine and alginate based inks for 3D bioprinters and characterization - Yalman, Volkan; Turkoglu, Nelisa; Sahin, Yesim Muege (ELSEVIER, 2025)
Three-dimensional (3D) printing is a rapidly evolving technology. This study focuses on developing biopolymeric inks tailored for Three-dimensional (3D) printing applications, specifically to produce 3D-printed materials for wound dressing. Humic Acid (HA) was incorporated into the ink formulations due to its anti-inflammatory properties. Although alginate-gelatine-based inks are widely available, no existing systems include HA as an additional component, underscoring the originality of this work.This innovation addresses a key challenge in wound care by promoting healing while minimizing inflammatory responses. Alginate(Alg) used in this study was extracted from Cystoseira barbata, a brown algae species collected from Gideros Bay in Kastamonu, located along Turkey's western Black Sea coast. This is the first study to purify alginate from algae sourced from this regio. The extraction process was optimized. Four biopolymeric ink formulations were prepared in the study and were used to print 3D-biomaterials, which underwent characterization focusing on basic physicochemical properties. Biocompatibility was evaluated through cell viability tests (MTT assays), and Immune response analysis was evaluated through inflammatory markers; pro-inflammatory cytokines (IL-1 beta, TNF alpha), and the anti-inflammatory cytokine (IL-10). In conclusion, this study successfully purified and characterized alginate from algae collected in a previously unstudied region, Gideros Bay. A novel ink formulation, incorporating humic acid, was developed and 3Dprinted for the first time. The results demonstrate that the printed materials in the study possess high potential for use as wound dressing materials, marking a significant contribution to the literature.
Keywords: Alginate; Gelatine; Humic acid; 3D bioprinting; HYDROGEL; COMPOSITE; CULTURE; VITRO; CA2+; Biochemistry & Molecular Biology; Chemistry; Polymer Science